INCREASING VALUE-BASED COMPANY POTENTIAL: THE GROUNDS OF A FULL-SCALE ASSESSMENT - Romans Dyakons; Vsevolods Karajevs; Rostislavs Kopitovs (Baltic Journal of Economic Studies)
The present study is a comprehensive evaluation of a business enterprise, with the objective of assisting its management in identifying and addressing the consequences of organisational difficulties, including the formation and distribution of the economic fund created as a result of the prevention of incurred losses. The subject of this assessment is the decision-making methodology, which serves as the basis for drawing conclusions about the states of the process and includes elements for training personnel involved in the implementation of the new version of the system. The objective of methodological foundations is to facilitate the timely identification of potential vulnerabilities that could lead to future losses in sustainability. From an organisational perspective, the conditions that facilitate the implementation of unproductive proposals are being circumvented. The object under discussion is a standardised, unique management tool developed for the purpose of assessing the operational states of an organisation. The objective of this study is to develop a procedure for identifying effective methods to enhance organisational performance, while preventing unauthorised disruption to the control system. The full-scale assessment is performed through three conceptual transitions. The first of these transitions is from the initial application points to the subsequent anomaly capability principles. Finally, the standard clauses are reached. The standard provides a detailed, step-by-step account of the organisation's status. A significant element of the investigation is the provision of decision-making based on objective ratios. In order to form objective conclusions regarding the state of the organisation, recommendations are made to recover the loss of value, taking into account the localisation of the places that lead to inefficiencies. The novelty of the study lies in the development of a comprehensive document containing instructions for experts on implementing measures aimed at improving performance by eliminating the shortcomings of the original version of the real control system. The existence of the standard allows for a well-founded conclusion to be drawn regarding the organisation's performance through a combination of cost indicators designed to meet conditionally specified standards and dimensionless indicators of process capability that belong to the category of objectively defined standards. This combination permits the unlocking of the organisation's growth potential in a novel environment through the synchronisation of performance standards and efficiency metrics. Consequently, the organisation is safeguarded from implementing ineffectual changes that could result in a reduction in efficiency.